Continuing professional education – a priority direction of improving the professional competence of doctors: experience, achievements, problems and prospects. - Pertseva , T.O.; Kuryata , O.V.; Konopkina, L.I.; Bielosludtseva , K.O.; Stadnichuk , G.M. (Medicni Perspektivi, 2021)
Continuing education in terms of improving the professional competence of doctors has a great importance. In May 2020 for the first time in Ukraine under conditions of quarantine connected with COVID-19 the Prydniprovsk Association of Internal Medicine Doctors organized a 2-day international conference on internal medicine in a web format. The purpose of the work was to organize, conduct, determine the effectiveness of the international conference of internists in online format and analyze the results of the survey of students. A questionnaire which included 28 test tasks was developed to obtain a feedback from the lecturers. The answers were analyzed and the reasons for possible errors were considered. The level of knowledge acquired by students is generally quite high; however, the most problematic issues were the most modern diagnostic methods in gastroenterology, ECG diagnostics, clinical pharmacology in cardiology and pulmonology. The prospect of developing a system of continuing professional education for internists is to improve teaching methods with the subsequent involvement of leading specialists in various therapeutic areas to cover current issues of medical science and practice.